Adubac¸ão nitrogenada em capins do gênero Urochloa implantados em consórcio com a cultura do milho - Costa, Nídia R. [UNESP]; Andreotti, Marcelo [UNESP]; Lopes, Keny S. M. [UNESP]; Dos Santos, Fernanda G. [UNESP]; Pariz, Cristiano M. [UNESP] (Revista Brasileira de Ciencias Agrarias, 2014)
In the integrated crop-livestock under no-till system, the choice of forage species intercropped with maize can lead to changes in pasture quality and response to nitrogen fertilization of the intercrop. The objective of this work was to evaluate in an clay soil, a kaolinitic, thermic typic dystrophic, the dry matter yield and chemical composition of two species of Urochloa grasses intercropped with corn submitted to N fertilization during two growing seasons in the Brazilian Cerrado of low altitude. The experimental design used was a completely randomized blocks with four replicates of factorial scheme 2 x 5. The treatments were composed by two species of Urochloa (U. brizantha cv. Xaraés and U. ruziziensis), intercropped with corn and fertilized with doses of N, at topdressing and after intercropping with corn (0, 50, 100, 150 e 200 kg N ha-1). After intercrop with corn, the pasture of U. brizantha cv. Xaraés in the autumn season presents highest dry matter yield and pasture of U. ruziziensis presents best chemical composition, with lower concentrations of fiber and higher concentrations of crude protein and total digestible nutrients, and higher dry matter digestibility. Pastures of U. brizantha cv. Xaraés and U. ruziziensis did not presents increase of the dry matter yield in the autumn season, when fertilized with nitrogen doses during and after intercrop with corn, under no-till system in transition/consolidation phase (5 to 10 years) in irrigated conditions of the Brazilian Cerrado of Mato Grosso do Sul state, with low altitude.
Nitrogen fertilization of Urochloa grasses intercropped with corn
Keywords: Chemical composition; Crop-livestock system; Nitrogen; Urochloa brizantha; Urochloa ruziziensis